Pemberdayaan UMKM Mama Ni Melalui Redesain Identitas Visual dan Kemasan Saset Berbasis Pendekatan Partisipatif untuk Memperkuat Daya Saing Produk Lokal - Karyn Ibreina Ginting; Yana Erlyana (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Institut Informatika Indonesia Surabaya, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in Indonesia’s economy, yet many still face challenges in visual identity, branding, and product packaging. Mama Ni, a sambal and seasoning producer from Malang, offers authentic flavors but lacks a competitive visual identity and packaging for modern markets. This community service project aimed to support Mama Ni through a participatory redesign of its visual identity and sachet packaging, rooted in local cultural elements. The activities included assessing partner needs, co-developing design concepts, creating a new visual identity that integrates the Kucecwara batik motif and an illustration of the owner as a brand icon, and testing the new packaging with consumer feedback. The project resulted in the creation of a new sub-brand, Nibumbu, accompanied by packaging for four flavor variants that is more attractive, informative, and professional. A survey of 108 respondents demonstrated improved consumer perceptions: 85% rated the new design as more visually appealing, 83% found the information clearer, 80% considered it more professional, and 82% expressed higher purchase interest compared to the old packaging. This program contributes to strengthening the competitiveness of local MSMEs through culturally grounded design and offers a replicable model for similar initiatives in other regions.